2020
DOI: 10.3390/cancers12071851
|View full text |Cite
|
Sign up to set email alerts
|

Desmoid-Type Fibromatosis

Abstract: Desmoid tumors represent a rare entity of monoclonal origin characterized by locally aggressive behavior and inability to metastasize. Most cases present in a sporadic pattern and are characterized by a mutation in the CTNNB1 gene; while 5–15% show a hereditary pattern associated with APC gene mutation, both resulting in abnormal β-catenin accumulation within the cell. The most common sites of presentation are the extremities and the thoracic wall, whereas FAP associated cases present intra-abdominally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 69 publications
2
86
0
7
Order By: Relevance
“…The apc (adenomatous polyposis coli) gene, which regulates degradation of beta-catenin, is also implicated [ 19 ]. Familial adenomatous polyposis (FAP), the resulting syndrome of apc mutation, accounts for 10% of desmoid tumours [ 5 ]. Desmoid tumours are 1000 times more common in those with FAP [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The apc (adenomatous polyposis coli) gene, which regulates degradation of beta-catenin, is also implicated [ 19 ]. Familial adenomatous polyposis (FAP), the resulting syndrome of apc mutation, accounts for 10% of desmoid tumours [ 5 ]. Desmoid tumours are 1000 times more common in those with FAP [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Desmoids are formed from the proliferation of myofibroblasts within connective tissue, resulting in a soft-tissue mass [ 5 ]. These tumours are most commonly found in the abdominal wall, mesentery, and limbs [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the role of postoperative adjuvant radiotherapy has been controversial in the past few decades. Different studies have come to different conclusions (28)(29)(30)(31). A meta-analysis has indicated that adjuvant radiotherapy can reduce the recurrence rate of patients with positive resection margins, but for patients with negative resection margins, adjuvant radiotherapy cannot reduce recurrence or improve the local control rate (32).…”
Section: Discussionmentioning
confidence: 99%
“…Desmoid tumors occur most often between the ages of 15 and 60, with a peak at 30 to 40 years old [1,4,5]. The tumor is benign and does not metastasize, but can invade nearby tissue aggressively and often painfully.…”
Section: Discussionmentioning
confidence: 99%